Effects of Audio - taped Instructional Package on Learners' Performance in Spoken English in Primary Schools of Akwa Ibom State - Asuquo, Eno Ndarake (2015)
This study examined the differences in the performance of learners of English Language exposed to Audio-taped Instructional package and those not exposed in the rural and urban schools of study. It also compared the performances of male and female learners in primary schools exposed to audio-taped instructional package in pronunciation of English language words and identified the effect of the use of audio-taped instructional package on learners' retention of lessons in pronunciation of English language words. This was with ultimate aim of improving the pupils' pronunciation of English Language